2017
DOI: 10.1186/s12888-017-1530-9
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of lipid metabolism abnormalities in APOE ε2-genotype and male patients 60 years or older with schizophrenia

Abstract: BackgroundSchizophrenia is a serious mental disorder largely manageable with atypical antipsychotics; however, these drugs have been associated with glucose/lipid metabolism issues such as diabetes and hyperlipidaemia. Apolipoprotein E (APOE) is the most abundant apolipoprotein, and APOE genotypes have been correlated with lipid metabolism phenotypes in an age-dependent manner. Studies examining the relationship between the APOE genotype and lipid abnormalities in patients with schizophrenia have been inconclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The human apolipoprotein E (ApoE) variant originates from two functional polymorphisms (rs429358 and rs7412) in exon 4 of the ApoE gene, which can be combined to form three major subtypes (2,3 and 4) [15]. Previous studies have shown that ApoE gene polymorphism may affect the level of lipoprotein [16][17][18] and also affect the development of schizophrenia [19,20]. For example, one study found a significant association between ApoE 3 gene variation and schizophrenia in Asian populations [19]; Another study found a significant association between ApoE rs429358 or ApoE rs7412 polymorphisms and low-density lipoprotein levels (LDL) in whites and African Americans [21].…”
Section: Introductionmentioning
confidence: 99%
“…The human apolipoprotein E (ApoE) variant originates from two functional polymorphisms (rs429358 and rs7412) in exon 4 of the ApoE gene, which can be combined to form three major subtypes (2,3 and 4) [15]. Previous studies have shown that ApoE gene polymorphism may affect the level of lipoprotein [16][17][18] and also affect the development of schizophrenia [19,20]. For example, one study found a significant association between ApoE 3 gene variation and schizophrenia in Asian populations [19]; Another study found a significant association between ApoE rs429358 or ApoE rs7412 polymorphisms and low-density lipoprotein levels (LDL) in whites and African Americans [21].…”
Section: Introductionmentioning
confidence: 99%
“…A complete physical examination, medical history, and laboratory tests were also performed for each subject. Detailed inclusion criteria and information collection process were introduced in our previous studies (33).…”
Section: Participants Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…This cross-sectional study was conducted between July 1, 2015, and December 31, 2015, and included 301 hospitalized elderly schizophrenics (age ranges from 60 to 92 years, with an average age of 67.31 ± 6.667; among them, 161 were males, accounting for 53.5%), who were recruited from three mental health centers (including the Shanghai Mental Health Center, the Mental Health Center of Fengxian District in Shanghai, and the Mental Health Center of Jiading District in Shanghai). The method of sampling has been described in our previous studies (14). The inclusion criteria were as follows: (1) aged 60 or more; (2) diagnosed with schizophrenia, which was diagnosed by a senior psychiatrist according to the International Classification of Diseases 10 diagnostic standard; (3) without major medical abnormalities, including unstable, acute, or life-threatening medical illness and central nervous system diseases; (4) was able to cooperate and complete relevant inspections.…”
Section: Participantsmentioning
confidence: 99%